A Misguided Contraindication: International Normalized Ratio in Acute Liver Failure Precluding Thrombolysis for Massive Pulmonary Embolism. Issue 4 (15th February 2019) - Long, Micah T.; Gallo, Paul D.; Hammel, Laura L.; Coursin, Douglas B.
Abstract : Massive pulmonary embolism and its treatment with thrombolysis both carry grave risks. Optimal management hinges on determining the risk-to-benefit ratio of thrombolytic administration. For patients with liver dysfunction, assessing bleeding risk is challenging because they may have elevations in the international normalized ratio yet be hypercoagulable. We describe a patient with massive pulmonary embolism and new-onset liver failure, who—absent contraindications—warranted thrombolysis. Initial laboratory values, however, revealed an elevated international normalized ratio, which precluded lysis, despite a hypercoagulable Thromboelastogram. We believe that viscoelastic testing of coagulation is essential for evaluating coagulation in liver dysfunction, particularly when considering thrombolysis.